Pityriasis rubra pilaris‐like reaction induced by imatinib. (18th June 2013) - Plana, A.; Carrascosa, J. M.; Vilavella, M.; Ferrandiz, C.
Summary Imatinib, a kinase inhibitor, is currently approved for the treatment of chronic myeloid leukaemia, gastrointestinal stromal tumours (GIST), and other malignant conditions such as dermatofibrosarcoma protuberans. Treatment with imatinib is generally well tolerated, but some cutaneous adverse events (AEs), such as exanthematous papular eruptions and Stevens–Johnson syndrome have been reported. We report a case of a pityriasis rubra pilaris (PRP)‐like eruption associated with this drug. Although cutaneous AEs associated with imatinib are relatively common (up to 69% of cases), no previous cases of PRP‐like eruptions related to this drug have been described previously, to our knowledge.